Evolution of the Dearomative Functionalization of Activated Quinolines and Isoquinolines: Expansion of the Electrophile Scope. (13th May 2022) - Kischkewitz, Marvin; Marinic, Bruno; Kratena, Nicolas; Lai, Yonglin; Hepburn, Hamish B.; Dow, Mark; Christensen, Kirsten E.; Donohoe, Timothy J.
Abstract: Herein we disclose a mild protocol for the reductive functionalisation of quinolinium and isoquinolinium salts. The reaction proceeds under transition‐metal‐free conditions as well as under rhodium catalysis with very low catalyst loadings (0.01 mol %) and uses inexpensive formic acid as the terminal reductant. A wide range of electrophiles, including enones, imides, unsaturated esters and sulfones, β‐nitro styrenes and aldehydes are intercepted by the in situ formed enamine species forming a large variety of substituted tetrahydro(iso)quinolines. Electrophiles are incorporated at the C‐3 and C‐4 position for quinolines and isoquinolines respectively, providing access to substitution patterns which are not favoured in electrophilic or nucleophilic aromatic substitution. Finally, this reactivity was exploited to facilitate three types of annulation reactions, giving rise to complex polycyclic products of a formal [3+3] or [4+2] cycloaddition. Abstract : Reductive functionalisation of quinolinium and isoquinolinium salts with formic acid as the terminal reductant was possible under transition‐metal‐free conditions or rhodium catalysis with very low catalyst loadings. A wide range of electrophiles, including enones, imides, unsaturated esters and sulfones, β‐nitrostyrenes and aldehydes, were intercepted by the enamine species formed in situ to generate substituted tetrahydro(iso)quinolines.